2021
DOI: 10.1111/ggi.14259
|View full text |Cite
|
Sign up to set email alerts
|

Associations between genetic loci related to lean mass and body composition in type 2 diabetes

Abstract: Aim: Several genetic loci related to lean mass have been identified in healthy individuals by genome-wide association studies; however, the contribution of these loci to body composition in type 2 diabetes remains to be investigated. Here, we aimed to clarify the genetic determinants of body composition in individuals with type 2 diabetes.Methods: A total of 176 Japanese outpatients (70 women and 106 men) with type 2 diabetes were studied using a cross-sectional design. Body composition was measured using bioi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…In a large meta-analysis of genomewide association studies for lean mass, VCAN loci (rs2287926) was identified and successfully replicated for whole body lean mass, and was important for sarcopenia diagnosis [30]. Moreover, a significant correlation between the VCAN loci and body fat mass in non-elderly individuals with T2D was also successfully replicated in another cross-sectional study [31]. FCRL1, a newly identified co-receptor of B cell receptors (BCR), was passively recruited into B cell immunological synapses upon BCR engagement in the absence of FCRL1 cross-linking, thus regulating B cell activation and function [32].…”
Section: Discussionmentioning
confidence: 89%
“…In a large meta-analysis of genomewide association studies for lean mass, VCAN loci (rs2287926) was identified and successfully replicated for whole body lean mass, and was important for sarcopenia diagnosis [30]. Moreover, a significant correlation between the VCAN loci and body fat mass in non-elderly individuals with T2D was also successfully replicated in another cross-sectional study [31]. FCRL1, a newly identified co-receptor of B cell receptors (BCR), was passively recruited into B cell immunological synapses upon BCR engagement in the absence of FCRL1 cross-linking, thus regulating B cell activation and function [32].…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, downregulation of ADAMTSL3 displayed poor prognosis in hepatocellular carcinoma, supporting its tumor-suppressive role (Zhou et al 2020). ADAMTSL3 was reported to be a contribution of genetic factors in type 2 diabetes patients (Minohara et al 2021).…”
Section: Discussionmentioning
confidence: 91%
“…3 Natural genetic variation analysis has also been used to explore the mechanism of diabetes and its complications and predict the disease risk. [4][5][6][7] An ideal T2DM animal model is an essential tool for studying the pathogenesis of diabetes and developing new drugs. The minipig T2DM model can simulate the pathogenesis of human T2DM better than other current models.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of genome‐wide association studies (GWAS) and single‐nucleotide polymorphism (SNP) analysis technology, hundreds of single‐nucleotide polymorphism (SNP) loci have been found to be closely related to human T2DM 3 . Natural genetic variation analysis has also been used to explore the mechanism of diabetes and its complications and predict the disease risk 4–7 …”
Section: Introductionmentioning
confidence: 99%